Histopathological Study Of Nano Cerium Oxide On Healing Of Corneal Ulcer In Rabbits - A Tlayeb, Enad; M. Hashim, Ammar (Journal of Neonatal Surgery, 2025)
Background: injury in the cornea in animals tend to heal delay due to a vascular structure. Therefore, treatments that accelerate the healing of cornea needs to investigated. Object: To enhancing and evaluation of the healing process of cornea injury through clinically, fluorescent dye, and histopathological examination. Materials & methods: twenty-eight adult rabbits were used in this study. Under general anesthesia, done induce cornea injury by NaOH 0.4%. the animals were divided in to three groups: Group (A) Negative control group (4 rabbits), (B) Control group (12 rabbits), (C) Treated group (12 rabbits). The animals were examined clinical during the studied period and histopathological evaluation was performed at 1st, 2nd, and 4th week post operation. Results: in all periods of study, show significant differences in the epithelial regeneration (P≥ 0.01) in the Nano treated groups. While stromal edema and inflammation were significantly improved only in the fourth week, where it shows a significant difference than the other periods of the study (P≤ 0.05). Conclusion: The Nano cerium oxide enhancing and accelerated the regeneration of cornea injury.